Technology transfer in biotechnology : (Wiley-VCH, 2009)
Here, the world's top experts impart their knowledge and experience, many in print for the first time. By considering developing country markets, this book is the first truly global guide to technology transfer, helping companies all around the world to avoid costly mistakes in product development and to recover investments quickly. Individual sections treat trade-related aspects of intellectual property rights, technology transfer in health and healthcare as well as in agriculture and the environment.